What drives mobile in-app purchases? An extended framework of in-app purchase and monetary effort - Costa, Vicente Xavier Cavaleiro (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Marketing Intelligence